Assessing institutional sanitation and its impact at a citywide level: an exploration of school sanitation in the Accra Metropolitan Area, Ghana - Nkonde, William; Furlong, Claire; Reed, Brian; Brdanovic, Damir (Frontiers in Environmental Science, 2025)
IntroductionExploring sanitation at a city scale is crucial due to approaches such as Citywide Inclusive Sanitation (CWIS). Sanitation impacts individuals, households and the whole city, as recognised by CWIS. The Shit Flow Diagram Graphic (SFDG) is the primary tool for citywide situation analysis. However, current SFDGs assume that individuals use only home toilets, overlooking the complexity of toilet usage, including public and workplace facilities. Our understanding of citywide sanitation flows is incomplete if analyses ignore the other toilets that people use. This study explored the impact of one type of institutional sanitation, school sanitation, on citywide sanitation flows.MethodsTo do this an overview and analysis of school sanitation at a citywide level was needed and a method to split the school pupils’ excreta flows was developed. Data was collected from secondary sources (e.g. from Ghana Statistical and Educational Services), structured observations (n = 26), and interviews with key informants (n = 15), headteachers (n = 26) and students (n = 39) from across Accra Metropolitan Area, Ghana. This data was used to construct three SFDGs, which were compared using Trend Graphs (graphs used to compare the state of sanitation across the different stages of the sanitation value chain).Results and DiscussionThe findings indicated that school sanitation was less safely managed than household sanitation and that SFDGs could be used assess school-level sanitation. Method development was crucial to accurately partition pupils’ excreta flows. While annual flows from schools appeared insignificant citywide, this seasonal flow could adversely affect public and environmental health during school terms. Therefore, it may be more important to consider the school population as a whole when thinking about the impact of school sanitation. This study highlights the importance of understanding where people spend their day and how this is related to the different sanitation systems they use; it demonstrates the need to move beyond household sanitation. This study successfully demonstrates the level of information that is needed regarding people’s sanitation practices which enables their excreta flows to be split between different facilities. It could be used as a guide for future studies and the further development of methods to explore this topic.